Analysis of Causal Factors of Bandung Raya and Turangga Train Accidents and Implementation of Passenger Safety Guarantees - devi rahma oktafia; ahmad mustofa (Journal Of Applied Multidisiplinary Studies, 2025)
This study provides an original contribution to the discourse on transportation safety by focusing on the specific case of the PT. KAI train accident in Cicalengka, Bandung, which highlights underexplored aspects of corporate responsibility in accident scenarios. The research objectives are to identify the root causes of the accident and to evaluate the responsibility measures undertaken by PT. KAI (Persero) in its aftermath. Employing a qualitative literature study method, this research synthesizes and analyzes data from various online media news texts to derive insights. Empirical results reveal that the accident was primarily caused by a combination of human error, infrastructure deficiencies, and procedural lapses, while PT. KAI demonstrated accountability through compensation programs, safety audits, and public communications. The implications of this study emphasize the need for strengthened safety assurance frameworks in transportation systems, including regular training and transparent reporting mechanisms, to mitigate future risks. This analysis offers practical recommendations for enhancing corporate accountability and operational safety in the railway sector.